Redefining the image of the contemporary city – changes in linguistic and cultural realms – preliminary remarks - Koszko, Marta (Scripta Neophilologica Posnaniensia, 2019)
Contemporary cosmopolitan European cities have been recently undergoing considerable social changes. Although most of them can be described as multicultural, the character of their public space should be redefined due to the intensified influx of immigrants mainly from the Middle East and North Africa and the socio-cultural background they bring along. This social and cultural process has a significant influence on the internal and external image and the identity of the city. These notions can be discussed in reference to Meffert’s (1989) concept of the city’s identity and the image of a city, hence in reference to the system of visual identification, communication system and the city culture. A particular attention should be drawn to the language in the public space (linguistic landscape LL), ritualized public space and the overall image of the city. These naturally have to be considered in the context of the socio-cultural transformation of the European cities. It should also be pointed out that Meffert’s theory may need to be slightly redefined in order to reflect the present-day urban cultural and linguistic reality.